Can prolongate use of social media immediately before training worsen high level male volleyball players` visuomotor skills? - Fortes, L. S.; Berriel, G. P.; Faro, H.; Freitas-Júnior, C. G.; Peyré-Tartaruga, L. A. (Perceptual and Motor Skills, 2022)
Our aim was to analyze the effect of mental fatigue caused by prolonged social media use on high-level volleyball players' visuomotor skills. Eighteen high-level male young volleyball players participated in this randomized, counterbalanced, crossover design. All participants underwent a 2-week experiment in which we measured their response times when performing a visuomotor task with and without mental fatigue inducement through repeated use of social media immediately before training sessions. In the control condition, participants watched TV for 30-minutes, and in the social media condition, they used a social media app (Instagram®) on smartphones for 30-minutes. We found a significant Condition x Time interaction on visuomotor task response time (p = 0.03), but there was no significant main effect of either Time or Condition. Mental fatigue, induced by repeated app-based social media use for 30-minutes immediately before training sessions, affected elite male volleyball players` visuomotor skills.